USE OF FORMATIVE ASSESSMENT AS AN EDUCATIONAL TOOL - Jain, Vaishali; Agrawal, Vandana; Biswas, Shubho (Journal of Ayub Medical College Abbottabad, 2012)
Background: Though formative assessments are popular in medical education, but data to establish their educational benefits are lacking. This study was conducted to determine whether participation and performance of MBBS students in regular formative assessments are associated with positive outcomes and has measurable effects on learning. Methods: One hundred and fifty MBBS students of semester II attending Biochemistry classes were studied by dividing into two groups till the completion of a topic. End-of-topic summative assessment marks were analysed with respect to the effect of participation and performance in formative assessments. Results: Participation in formative assessments had a statistically significant positive relationship with summative assessment marks. Mean difference in formative and summative assessment marks for group that participated in formative assessments is 1.6 (95% CI=0.9-2.4, p<0.001). The mean difference in summative assessment marks for two groups is 3.4 (95% CI=2.3-4.6, p<0.001). The mean difference in marks obtained by solving case studies given in Summative Assessment for two groups is 1.2 (95% CI=0.7-1.6, p<0.001). Conclusions: Formative assessment not only assesses students’ achievements but it also enables students to recognise the areas in which they are having difficulty and to concentrate their future efforts on those areas. Adequate frequency of formative assessment with immediate feedback is beneficial as it stimulates meaningful and multifaceted learning. The results of this study encourage the use of formative assessment as an educational tool in all MBBS subjects for they have significant positive effects on learning. Keywords: Formative assessment, Summative assessment, Performance, Feedback